Kajian Risiko Bencana Kebakaran pada Kawasan Permukiman Padat di Kecamatan Samarinda Ulu, Kota Samarinda - Afanggi Oktavian; Mardwi Rahdriawan (Jurusan Perencanaan Wilayah dan Kota, 2023)
The high population density causes residential areas to become dense and irregular. Dense and irregular residential areas create the condition of electricity network seems tangled, it is very prone to causing short circuits which can trigger a residential fire. Samarinda Ulu District has the highest population density in Samarinda City, which has occurred 34 residential fire cases in 2020. Therefore this research was conducted to determine the level of residential fire disaster risk for each sub-district in Samarinda Ulu District based on the analysis results of hazard, vulnerability, and capacity of residential fire disaster. This research used a quantitative method with a matrix approach based on the scoring process through a descriptive statistical analysis to classify the level of residential fire disaster risk. The result of this research found that Jawa and Bukit Pinang Sub-Districts have a high level of residential fire disaster risk in the Samarinda Ulu District. The high level of residential fire disaster risk concludes the area has low resilience to minimize potential damage and losses due to a residential fire disaster caused by the low ability to protect and handlethe fire residential hazard.